The impact of competitive category on characteristics of gut microbiome in Japanese elite para-athlete - Akazawa, N.; Nakamura, M.; Tanimura, Y.; Kojima, C.; Motonaga, K.; Hakamada, N.; Shimizu, K. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Deterioration of physical condition causes not only decreased physical fitness but also immunodeficiency, digestive dysfunction, and gastrointestinal complaints (abdominal pain, diarrhea, constipation, etc.). Some individuals with lower limb dysfunction have been often in trouble about defecation and gut dysbiosis, which are related to some symptoms such as fatigability, mood disturbance, and metabolic disorder. However, it is not understood the gastrointestinal condition and gut microbiome in sitting category para-athletes. The aim of the present study was to investigate the impact of competitive category on gut microbiome in para-athletes. METHODS: Eighteen Japanese elite para-athletes were participated in the study and were divided to the sitting category and the standing category. We analyzed their gut microbiome using 16S rRNA sequencing and evaluated the abundance at genus level and the alpha diversity evenness. RESULTS: The abundance of Bacteroides genus was significantly higher and Prevotella genus was significantly lower in the sitting category group than that of the standing category group (21.7 ± 9.5 vs. 8.0 ± 6.4 % and 0.2 ± 0.4 vs. 10.7 ± 11.4 % respectively, p < 0.05). The diversity of gut microbiome was significantly lower in the sitting category group than in the standing category group (0.79 ± 0.03 vs. 0.81 ± 0.02 U, p < 0.05). CONCLUSION: These findings suggested that para-athletes have a different gut microbiome profile between competitive categories. Gut microbiota dysbiosis is associated with neurological dysfunction and deterioration of host homeostasis. Therefore, gastrointestinal status may be an important factor for maintaining condition in sitting category para-athletes.